Exploring repurchase intentions for Wardah sunscreen in Padang city: the impact of brand awareness, social influence, and perceived quality - Fitri adilla.Y; Arief Maulana (Marketing Management Studies, 2023)
Study This aim for analyze the influence of brand awareness, social influence, and perceived quality on the repurchase intention of consumer Wardah sunscreen products in Padang City. The population of this study were female consumers of wardah sunscreen in the city of Padang. Amount study This were 260 respondents. Data was collected through online questionnaire distribution and data processing was carried out with using SPSS software . Results study This show that (1) Brand Awareness has a positive and significant effect on Repurchase Intention, (2) Social Influence positive effect and significant on Repurchase intention, (3) Perceived Quality has a positive and significant effect on Repurchase Intention. (4) Brand Awareness, Social Influence, Perceived Quality have a positive and significant effect on Repurchase Intention.